Prodromal neuroinvasion of pathological α-synuclein in brainstem reticular nuclei and white matter lesions in a model of α-synucleinopathy. Issue 2 (14th May 2021) - Ferreira, Nelson; Richner, Mette; van der Laan, Amelia; Bergholdt Jul Christiansen, Ida; Vægter, Christian B; Nyengaard, Jens R; Halliday, Glenda M; Weis, Joachim; Giasson, Benoit I; Mackenzie, Ian R; Jensen, Poul H; Jan, Asad
Abstract: Neuropathological observations in neurodegenerative synucleinopathies, including Parkinson disease, implicate a pathological role of α-synuclein accumulation in extranigral sites during the prodromal phase of the disease. In a transgenic mouse model of peripheral-to-central neuroinvasion and propagation of α-synuclein pathology (via hindlimb intramuscular inoculation with exogenous fibrillar α-synuclein: the M83 line, expressing the mutant human Ala53Thr α-synuclein), we studied the development and early-stage progression of α-synuclein pathology in the CNS of non-symptomatic (i.e. freely mobile) mice. By immunohistochemical analyses of phosphroylated α-synuclein on serine residue 129 (p-S129), our data indicate that the incipient stage of pathological α-synuclein propagation could be categorized in distinct phases: (i) initiation phase, whereby α-synuclein fibrillar inoculum induced pathological lesions in pools of premotor and motor neurons of the lumbar spinal cord, as early as 14 days post-inoculation; (ii) early central phase, whereby incipient α-synuclein pathology was predominantly detected in the reticular nuclei of the brainstem; and (iii) late central phase, characterized by additional sites of lesions in the brain including vestibular nuclei, deep cerebellar nuclei and primary motor cortex, with coincidental emergence of a sensorimotor deficit (mild degree of hindlimb clasping). Intriguingly, we also detected progressive α-synuclein pathology in premotor and motor neurons in the thoracic spinal cord, which does not directly innervate the hindlimb, as well as in the oligodendroglia within the white matter tracts of the CNS during this prodromal phase. Collectively, our data provide crucial insights into the spatiotemporal propagation of α-synuclein pathology in the nervous system of this rodent model of α-synucleinopathy following origin in periphery, and present a neuropathological context for the progression from pre-symptomatic stage to an early deficit in sensorimotor coordination. These findings also hint towards a therapeutic window for targeting the early stages of α-synuclein pathology progression in this model, and potentially facilitate the discovery of mechanisms relevant to α-synuclein proteinopathies. In a rodent model of synucleinopathy, Ferreira et al., delineate the spatiotemporal progression of incipient α-synuclein pathology (of peripheral origin) in the CNS. The authors show early affection of brainstem reticular nuclei in non-paralyzed mice, and pathological white matter lesions in relation to the neuronal pathology. Abstract : In a rodent model of synucleinopathy, Ferreira et al., delineate the spatiotemporal progression of incipient α-synuclein pathology (of peripheral origin) in the CNS. The authors show early affection of brainstem reticular nuclei in non-paralyzed mice, and pathological white matter lesions in relation to the neuronal pathology. Graphical Abstract: